Autonomous Fire Detection Robot Using Modified Voting Logic - Rehman, Adeel ur (Université d'Ottawa / University of Ottawa, 2015)
Recent developments at Fukushima Nuclear Power Plant in Japan have created urgency in the scientist community to come up with solutions for hostile industrial environment in case of a breakdown or natural disaster. There are many hazardous scenarios in an indoor industrial environment such as risk of fire, failure of high speed rotary machines, chemical leaks, etc. Fire is one of the leading causes for workplace injuries and fatalities. The current fire protection systems available in the market mainly consist of a sprinkler systems and personnel on duty. In the case of a sprinkler system there could be several things that could go wrong, such as spraying water on a fire created by an oil leak may even spread it, the water from the sprinkler system may harm the machinery in use that is not under the fire threat and the water could potentially destroy expensive raw material, finished goods and valuable electronic and printed data. There is a dire need of an inexpensive autonomous system that can detect and approach the source of these hazardous scenarios. This thesis focuses mainly on industrial fires but, using same or similar techniques on different sensors, may allow it to detect and approach other hostile situations in industrial workplace. Autonomous robots can be equipped to detect potential threats of fire and find out the source while avoiding the obstacles during navigation. The proposed system uses Modified Voting Logic Fusion to approach and declare a potential fire source autonomously. The robot follows the increasing gradient of light and heat intensity to identify the threat and approach the source.
Keywords: Autonomous robot; Sensor fusion; Fire detection; Modified Voting Logic; Voting Logic; LabVIEW